Recommended Clauses for Green Consultancy Contract in the Construction Sector - Hansen, Seng; Bintang Koesalamawardi, Ario; Sandrica Ng, Yoshie (UIR Press, 2025)
It is undeniable that the construction industry has a significant impact on the destruction of the natural environment. Therefore, policy makers and key stakeholders are trying to overcome the impact of the construction sector through the implementation of the green building concept in every stage of construction work. However, this effort encounters various obstacles such as low understanding of green building, low participation in implementing green building concept, and the emergence of various risks in green building projects. This study aims to investigate the contractual aspects of green building projects through a comprehensive approach that includes integrative literature reviews, questionnaire surveys, and a focus group discussion. This study found eleven contractual issues of green consultancy contracts. Furthermore, based on these findings, various clauses were developed that were recommended to be included in the green consultancy contracts. This research is useful for the body of knowledge related to the development of green consultancy contracts in the construction sector. Practically, the results of this study can be used directly by green building consultants in negotiating their contracts with the employer.